Analyzing the effects of father's antisocial behavior on mothers and children: a longitudinal study of single-parent families - Fisher, Marlene Renee (1997)
This study examines changes in mothers' and adolescent mental health and behavioral measures in recently divorced single parent families. Overall, mothers in the study showed improvement in multiple measures of mental health over the course of this three year study. Single mother's problems with drinking also improved over time. Lower income women whose former spouse had problems with alcohol showed the most improvement in anxiety over time. Women who reported more physically abusive behavior prior to their divorce also reported the most improvement in depression over time. Women who continued to experience abuse in the post-divorce setting continued to have more problems with substance use, anxiety, and depression compared to other groups in the study. Mothers' reports of their former spouse problems with substance use predicted differences or changes in adolescent delinquency, antisocial behavior, and mastery. Mothers' reports of emotional abuse prior to the divorce predicted differences or changes in adolescent anxiety, depression, delinquency, antisocial behavior and drug use. Mothers' report of the former spouses' physically abusive behavior predicted differences or changes in adolescent antisocial behavior, while targets' report of witnessing physical abuse by the father produced different outcomes in self-esteem by gender. Targets' report of witnessing emotional abuse by the father predicted significant differences or changes over time in self-esteem, anxiety, depression, and antisocial behavior. Father's level of post-divorce abusive behavior to adolescents was significantly related to differences or changes in adolescent mastery, anxiety, self-esteem, delinquency, and drug use